2023
DOI: 10.3389/fonc.2023.1099731
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between microwave ablation and ferroptosis: The next hot topic?

Abstract: Microwave ablation has been one form of thermal ablation in treatments for many tumors, which can locally control unresectable tumors. Ferroptosis is iron-dependent cell death caused by the cumulative reactive oxygen species and lipid peroxidation products. Recently, increasing evidence has shown that ferroptosis might play a vital role in MWA-induced tumor suppression. In this article, we briefly illustrate the concept of ferroptosis, the related signal pathways and inducers, the basic principle of microwave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…This mechanism could play a role in the tumor-killing effects of MWA ( Bozaykut et al, 2016 ). Research indicates that inducing ferroptosis is a promising therapy for cancer treatment, suggesting that combining MWA with ferroptosis inducers could be a novel approach in tumor therapy ( Gai et al, 2020 ; Yu et al, 2023 ). In conclusion, the specific ablation of TAU, Shank3, and GPX4, along with utilizing MWA technology, presents new opportunities for studying ND and cancer induced by ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism could play a role in the tumor-killing effects of MWA ( Bozaykut et al, 2016 ). Research indicates that inducing ferroptosis is a promising therapy for cancer treatment, suggesting that combining MWA with ferroptosis inducers could be a novel approach in tumor therapy ( Gai et al, 2020 ; Yu et al, 2023 ). In conclusion, the specific ablation of TAU, Shank3, and GPX4, along with utilizing MWA technology, presents new opportunities for studying ND and cancer induced by ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…When local tissues are damaged, hyaluronic acid and markers of endothelial damage become exposed. This stimulates the production of chemokines and vascular adhesion molecules, which in turn recruit immune cells to the affected site ( 35 ). In a clinical study on breast cancer patients, MWA was found to significantly induce increased levels of ICOS+ activated CD4 + T cells and serum IFN-γ, indicating a multifaceted impact on the local and systemic levels beyond coagulation necrosis and protein degeneration ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to heat-induced apoptosis and necrosis, Yu et al speculated that MWA might induce ferroptosis, a newly proposed type of cell death, through the induction of reactive oxygen species, p53, the heat-shock protein, and NF-E2 related factor 2 (NRF2) [49]. Accumulating evidence suggests that ferroptotic cells attract and activate innate immune cells, such as neutrophils, and are efficiently engulfed by phagocytes [50].…”
Section: Mwamentioning
confidence: 99%